Inhibition of heat-labile toxin from Bordetella parapertussis by fatty acids. - Endoh, M (1990)
The ability of heat-labile toxin (HLT) from Bordetella parapertussis to induce skin lesions in guinea pigs was found to be inhibited by lipids isolated from skin layers of adult mice, which are refractory to the lesion-inducing activity of HLT. These lipids were identified as linoleic and oleic acids. Other long-chain unsaturated fatty acids were also found to inhibit HLT; however, fatty alcohols, neutral lipids, phospholipids, cholesterol, prostaglandin, and leukotriene had no measurable effects on HLT action. The data presented in this report indicate that the ability of HLT to induce skin lesions in animals may depend, at least in part, on the free fatty acid content of the skin layer.